1999
DOI: 10.1046/j.1439-0264.1999.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Study of the Extensor Digitorum Longus and Soleus Muscles in Alcoholic Rats

Abstract: The extensor digitorum longus (EDL) and soleus (SOL) muscle fibres from albino rats submitted to experimental chronic alcoholism were evaluated in accordance with their metabolic and morphometric profiles. Twenty-seven male animals aged 4 months and weighing approximately 400 g were used. The animals were divided into three groups: control, isocaloric and alcoholic and sacrifices were carried out after 5, 10 and 15 months. The muscles were dissected, removed, cross-sectioned in a cryostat and submitted to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…1 and 2, it can be concluded that high oxidative fibers are generally smaller and also contain more 18S RNA, α-sk actin-, MuRF1- and MAFbx-mRNA, compared to low oxidative fibers. The literature on rat SO and EDL fiber type composition does not unambiguously show that high oxidative fibers have smaller CSA compared to low oxidative fibers (Deveci et al 2001 ; Kupa et al 1995 ; Torrejais et al 1999 ). The inconsistencies in CSA data of the latter studies compared to other studies with a more systematic approach (Armstrong and Phelps 1984 ; Nakatani et al 1999 ) may be related to age, gender, muscle region or the effect of treatment.…”
Section: Fiber Type-related Differences In the Machinery For Protein mentioning
confidence: 98%
“…1 and 2, it can be concluded that high oxidative fibers are generally smaller and also contain more 18S RNA, α-sk actin-, MuRF1- and MAFbx-mRNA, compared to low oxidative fibers. The literature on rat SO and EDL fiber type composition does not unambiguously show that high oxidative fibers have smaller CSA compared to low oxidative fibers (Deveci et al 2001 ; Kupa et al 1995 ; Torrejais et al 1999 ). The inconsistencies in CSA data of the latter studies compared to other studies with a more systematic approach (Armstrong and Phelps 1984 ; Nakatani et al 1999 ) may be related to age, gender, muscle region or the effect of treatment.…”
Section: Fiber Type-related Differences In the Machinery For Protein mentioning
confidence: 98%
“…MFCS of the extensor carpi radialis longus muscle is reportedly circular in 12-day-old rats, but polygonal in rats aged ≥23 days 1 ) . Torrejais et al 2 ) examined frozen slices of the extensor digitorum longus and soleus muscles stained with nicotinamide adenine dinucleotide and reported, as part of their subjective findings, that they observed polygonal, triangular, and circular shapes in the MFCS.…”
Section: Introductionmentioning
confidence: 99%